New wrinkles in lipoprotein lipase biology - Davies, Brandon S.J. (2012)
PURPOSE OF REVIEW: We summarize recent progress on GPIHBP1, a molecule that transports lipoprotein lipase (LPL) to the capillary lumen, and discuss several newly studied molecules that appear important for the regulation of LPL activity. RECENT FINDINGS: LPL, the enzyme responsible for the lipolytic processing of triglyceride-rich lipoproteins, interacts with multiple proteins and is regulated at multiple levels. Several regulators of LPL activity have been known for years and have been investigated thoroughly, but several have been identified only recently, including an endothelial cell protein that transports LPL to the capillary lumen, a microRNA that reduces LPL transcript levels, a sorting protein that targets LPL for uptake and degradation, and a transcription factor that increases the expression of apolipoproteins that regulate LPL activity. SUMMARY: Proper regulation of LPL is important for controlling the delivery of lipid nutrients to tissues. Recent studies have identified GPIHBP1 as the molecule that transports LPL to the capillary lumen, and have also identified other molecules that are potentially important for regulating LPL activity. These new discoveries open new doors for understanding basic mechanisms of lipolysis and hyperlipidemia.